The Politics of Public Piety and Socio-Religious Fragmentation: The Paradox of the Masjid Paripurna Program in Pekanbaru - Kasmuri Kasmuri; Masbukin Masbukin; Imam Hanafi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines how the Paripurna Mosque Program, initiated by the Pekanbaru City Government as part of the Madani City agenda, institutionalizes public piety and reshapes the relationship between religion, the state, and society. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving government officials, mosque managers, imams, congregants, and community leaders. Guided by the concepts of public piety and the public sphere, this study explores the sociopolitical implications of state involvement in mosque management. The findings indicate that state intervention is carried out through the appointment of religious personnel, public funding, reporting mechanisms, and institutional oversight. These arrangements strengthen mosque administration and support religious activities, while also creating new forms of symbolic differentiation based on access to resources, public recognition, and religious legitimacy. As a result, religious authority and institutional status become subjects of negotiation among religious actors and local communities. Rather than producing simple social fragmentation, the program creates dynamics of social-religious differentiation and contestation over legitimacy within the religious public sphere. This study contributes to the sociology of religion by demonstrating how local religious policies function as mechanisms to institutionalize public piety and reshape the relationships between state power, religious legitimacy, and community life in contemporary urban Indonesia